2019
DOI: 10.3390/nu11112755
|View full text |Cite
|
Sign up to set email alerts
|

Mumefural Ameliorates Cognitive Impairment in Chronic Cerebral Hypoperfusion via Regulating the Septohippocampal Cholinergic System and Neuroinflammation

Abstract: Chronic cerebral hypoperfusion (CCH) causes cognitive impairment and neurogenic inflammation by reducing blood flow. We previously showed that Fructus mume (F. mume) improves cognitive impairment and inhibits neuroinflammation in a CCH rat model. One of the components of F. mume, Mumefural (MF), is known to improve blood flow and inhibit platelet aggregation. Whether MF affects cerebral and cognitive function remains unclear. We investigated the effects of MF on cognitive impairment and neurological function-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…MF, a component of Japanese apricot juice concentrate PMFE [ 17 , 23 , 24 ], is well known to inhibit platelet aggregation [ 18 ], improve cognitive impairment [ 21 ], and have various beneficial effects [ 20 , 25 , 26 , 27 ]. In this study, we showed the anti-thrombotic efficacy and anti-inflammatory effects of MF in an FeCl 3 -induced thrombosis model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MF, a component of Japanese apricot juice concentrate PMFE [ 17 , 23 , 24 ], is well known to inhibit platelet aggregation [ 18 ], improve cognitive impairment [ 21 ], and have various beneficial effects [ 20 , 25 , 26 , 27 ]. In this study, we showed the anti-thrombotic efficacy and anti-inflammatory effects of MF in an FeCl 3 -induced thrombosis model.…”
Section: Discussionmentioning
confidence: 99%
“…P. mume fruit containing MF is widely used as a health food, especially in Japan [ 18 , 19 , 20 ]. We have previously shown that MF ameliorates cognitive impairment resulting from reduced cerebral blood flow by modulating the cholinergic system and neuroinflammation [ 21 ]. Although there are few studies on the efficacy of MF to date, it is expected to have an excellent effect on inhibiting platelet activity and suppressing inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroin ammation can trigger cognitive impairment, and the role of in ammasome NLRP3 processes involved in recognition impairment in a variety of nervous system diseases, has been supported by experimental evidence, especially in recent years. Several studies have shown that NLRP3 can be a target for improving memory impairment in diabetes [28][29][30][31], sepsis-associated encephalopathy [32], hypoxemia [33], epilepsy [34,35], AD [36,37], intracerebral hemorrhage [38], cerebral ischemia [39], and aged [40]. Baicalin increases the performance of APP/PS1 transgenic mice in MWM by suppressing NLRP3 in ammasomes to alleviate microglia-mediated neuroin ammation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described ( 30 ). Tissues were homogenized on ice in radio-immunoprecipitation assay (RIPA) buffer, and equivalent amounts of samples were fractionated by sodium dodecyl sulfate (SDS)–gel electrophoresis, transferred onto polyvinylidene difluoride membranes, and blocked with 5% nonfat milk in phosphate-buffered saline containing Tween-20.…”
Section: Methodsmentioning
confidence: 99%